Achieving highly efficient and selective cesium extraction using 1, 3-di-octyloxycalix[4]arene-crown-6 in n-octanol based solvent system: experimental and DFT investigation. Issue 35 (16th June 2021) - Patra, Kankan; Sadhu, Biswajit; Sengupta, Arijit; Patil, C. B.; Mishra, R. K.; Kaushik, C. P.
Abstract : Separation scheme was developed for selective extraction of long-lived fission product 137 Cs using substituted calix crown 6 ether from aqueous acidic solution. Abstract : Due to the long half-life of 137 Cs ( t 1/2 ∼ 30 years), the selective extraction of cesium (Cs) from high level liquid waste is of paramount importance in the back end of the nuclear fuel cycle to avoid long term surveillance of high radiotoxic waste. As 1, 3-di-octyloxycalix[4]arene-crown-6 (CC6) is suggested to be a promising candidate for selective Cs extraction, the improvement in the Cs extraction efficiency by CC6 has been investigated through the optimization of the effect of dielectric media on the extraction process. The effects of the feed acid (HNO3, HCl, and HClO4 ) and the composition of the diluents for the ligand in the organic phase on the extraction efficiency of Cs have been investigated systematically. In 100% n -octanol medium, Cs is found to form a 1 : 1 ion-pair complex with CC6 (0.03 M) providing a very high distribution ratio of D Cs ∼ 22, suggesting n -octanol as the most suitable diluent for Cs extraction. No significant interference of other relevant cations such as Na, Mg and Sr was observed on the D Cs value in the optimized solvent system. Density functional theory (DFT) based calculations have been carried out to elucidate the reason of ionic selectivity and enhanced Cs extraction efficiency of CC6 in the studied diluent systems. In addition to the ionic size-based selectivity of the crown-6 cavity, the polarity of the organic solvent system, the hydration energy of the ion, and the relative reorganization of CC6 upon complexation with Cs are understood to have roles in achieving the enhanced efficiency for the extraction of Cs by the CC6 extractant in nitrobenzene medium.